Assessment of Clinical Features Responsible for Ectopic Pregnancy - Nisha Tabassum, Paras Mangi, Syeda Sana Ali, Bazla Younas, Ayisha Raja, Ambreen Shabbir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ectopic pregnancy is a lethal condition and a gynecological emergency. It is associated with maternal morbidity and mortality with pregnancy loss. The incidence of ectopic pregnancy is increasing worldwide. The diagnosis of the ectopic pregnancy can be difficult without the suspicion of the condition. It is confused with the pelvic inflammatory disease and miscarriage. Objective: This study may help on formulating a guiding principle on the diagnosis and management of Ectopic pregnancies in this area. In this research the frequency of clinical presentations and factors responsible for ectopic pregnancy are determined. Methodology: This is a cross-sectional based study. This study was conducted at the Obstetricians and gynecology department of Murshid Hospital and health care Center Karachi. The 125 women diagnosed with ectopic pregnancy for the duration of six months from July 2021 to December 2021were included. Patients were examined for outcome variables (abdominal pain, vaginal bleeding, history of infertility, use of IUCD and previous ectopic pregnancy) noted in predesigned performa. Results: - The women mean age was 9m31 ± 6.6 years. There were 96 (78.4%) women observed with abdominal pain and 72 (57.6%) women with vaginal bleeding in which some of them had both clinical presentations. History of fertility 34 (27.2%), use of intrauterine contraceptive device 58 (46.4%) and previous ectopic pregnancy 33 (26.4%) were responsible for ectopic pregnancy. Conclusion: Majority of the patients attended the hospital were in acute condition. They were diagnosed with classical features of ruptured ectopic pregnancy. The most common clinical features were use of IUD, infertility history, and previous ectopic pregnancy. . For reducing the morbidity and mortality rates associated with the ectopic pregnancy the early diagnosis of the tubal rupture is an essential factor. Keywords: Ectopic pregnancy, vaginal bleeding, intrauterine contraceptive device